Recombinant Spider Silk Protein Matrices Facilitate Differentiation of Neural Stem Cells Into Mature and Functional Neurons - Lewicka, Michalina; Rebellato, Paola; Lewicki, Jakub; Uhlén, Per; Rising, Anna; Hermanson, Ola (Frontiers in Materials, 2021)
Neural stem cells (NSCs) show great promise in drug discovery and clinical application. Yet few efforts have been made to optimize biocompatible materials for such cells to be expanded and used in clinical conditions. We have previously demonstrated that NSCs are readily cultured on substrates of certain recombinant spider silk protein without addition of animal- or human-derived components. The question remains however whether this material allows differentiation into functional neurons, and whether such differentiation can take place also when the NSCs are cultured not only upon but also within the biodegradable material. Here we demonstrate that “foam”-like structures generated from recombinant spider silk protein (4RepCT) provided excellent matrices for the generation and multicellular analysis of functional excitatory neurons from NSCs without addition of animal- or human-derived components. NSCs isolated from the cerebral cortices of rat embryos were cultured at either 4RepCT matrices shaped as foam-like structures without coating, or on conventional polystyrene plates coated with poly-L-ornithine and fibronectin. Upon treatment with recombinant proteins including the extracellular signaling factor BMP4 or a combination of BMP4 and the signaling factor Wnt3a, the cortical NSCs cultured in 4RepCT foam-like structures differentiated efficiently into neurons that responded to glutamate receptor agonists, such as AMPA, to the same extent as control cultures. Matrices derived from recombinant spider silk proteins thus provide a functional microenvironment for neural stem cells with little or no animal- or human-derived components and can be employed in the development of new strategies in stem cell research and tissue engineering.